2022
DOI: 10.1001/jamanetworkopen.2021.43582
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of US Preventive Services Task Force Guideline–Concordant Cervical Cancer Screening Rates and Reasons for Underscreening by Age, Race and Ethnicity, Sexual Orientation, Rurality, and Insurance, 2005 to 2019

Abstract: IMPORTANCECervical cancer screening rates are suboptimal in the US. Population-based assessment of reasons for not receiving screening is needed, particularly among women from historically underserved demographic groups. OBJECTIVE To estimate changes in US Preventive Service Task Force guideline-concordant cervical cancer screening over time and assess the reasons women do not receive up-to-date screening by sociodemographic factors. DESIGN, SETTING, AND PARTICIPANTS This pooled population-based cross-sectiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
88
3
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(98 citation statements)
references
References 30 publications
6
88
3
1
Order By: Relevance
“…Their study shows that individuals who identify as a sexual minority are significantly less likely to have ever undergone cervical cancer screening in comparison with heterosexual individuals; furthermore, although most individuals who identify as a sexual minority are less likely to undergo screening for cervical cancer, regardless of their racial/ethnic backgrounds, those identifying as both Hispanic and a sexual minority have the lowest odds of ever undergoing cervical cancer screening in comparison with non-Hispanic White heterosexual individuals. The finding that sexual minority status is associated with low rates of cervical cancer screening concurs with other studies [3][4][5][6][7][8][9][10][11][12] and highlights the need to better understand cervical cancer screening practices among individuals who identify as a sexual minority so that we can address this disparity and improve cervical cancer screening in this population.…”
supporting
confidence: 86%
See 1 more Smart Citation
“…Their study shows that individuals who identify as a sexual minority are significantly less likely to have ever undergone cervical cancer screening in comparison with heterosexual individuals; furthermore, although most individuals who identify as a sexual minority are less likely to undergo screening for cervical cancer, regardless of their racial/ethnic backgrounds, those identifying as both Hispanic and a sexual minority have the lowest odds of ever undergoing cervical cancer screening in comparison with non-Hispanic White heterosexual individuals. The finding that sexual minority status is associated with low rates of cervical cancer screening concurs with other studies [3][4][5][6][7][8][9][10][11][12] and highlights the need to better understand cervical cancer screening practices among individuals who identify as a sexual minority so that we can address this disparity and improve cervical cancer screening in this population.…”
supporting
confidence: 86%
“…Although a lack of knowledge is a commonly identified barrier to cervical screening, individuals identifying as lesbian, gay, bisexual, transgender, queer, and other nonheterosexual orientations (LGBTQ+) are less likely than heterosexual individuals to report a lack of knowledge as a barrier. 9 Among lesbians, a lower rate of hormonal contraceptive use and fewer positive health beliefs (such as perceived benefit of screening) explain close to the half of the disparities in cervical screening utilization in comparison with heterosexual women. 5 Misinformation related to cervical cancer risk has been noted for health care providers and individuals identifying as FTM.…”
mentioning
confidence: 99%
“…A recent study reported that the most common reason for not receiving timely screening was lack of screening knowledge [ 66 ]. Addressing disparities in HPV awareness and knowledge and cervical cancer screening behaviors is important for caregivers because this population needs additional support to promote their optimal health given their at-risk health condition and crucial role in care recipients’ health [ 67 , 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…Addressing disparities in HPV awareness and knowledge and cervical cancer screening behaviors is important for caregivers because this population needs additional support to promote their optimal health given their at-risk health condition and crucial role in care recipients’ health [ 67 , 68 ]. Determining which caregiver subgroups are overdue for cervical cancer screenings could inform relevant stakeholders, including clinicians, who have a primary role in recommending screening to eligible caregivers [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…52 More recently, Suk et al showed that those of Asian ethnicity had higher rates of overdue cervical cancer screening compared to non-Hispanic White individuals with lack of knowledge reported as the biggest barrier to receiving timely screening across all study groups, further highlighting the gaps in health literacy and the important role PNs can play in cancer screening of IRPs. 72 At a healthcare systems' level, lack of patient education material based on their health literacy is a barrier, and we must develop patient education material focusing on various health literacy levels, and utilization of PNs in patient education may temporarily overcome some of the existing barriers.…”
Section: The Paucity Of Health Literacy-led Cancer Education Tools An...mentioning
confidence: 99%